FTY720 in immuno-regenerative and wound healing technologies for muscle, epithelial and bone regeneration - Behara, Monica; Goudy, Steven (Frontiers in Physiology, 2023)
In 2010, the FDA approved the administration of FTY720, S1P lipid mediator, as a therapy to treat relapsing forms of multiple sclerosis. FTY720 was found to sequester pro-inflammatory lymphocytes within the lymph node, preventing them from causing injury to the central nervous system due to inflammation. Studies harnessing the anti-inflammatory properties of FTY720 as a pro-regenerative strategy in wound healing of muscle, bone and mucosal injuries are currently being performed. This in-depth review discusses the current regenerative impact of FTY720 due to its anti-inflammatory effect stratified into an assessment of wound regeneration in the muscular, skeletal, and epithelial systems. The regenerative effect of FTY720 in vivo was characterized in three animal models, with differing delivery mechanisms emerging in the last twenty years. In these studies, local delivery of FTY720 was found to increase pro-regenerative immune cell phenotypes (neutrophils, macrophages, monocytes), vascularization, cell proliferation and collagen deposition. Delivery of FTY720 to a localized wound environment demonstrated increased bone, muscle, and mucosal regeneration through changes in gene and cytokine production primarily by controlling the local immune cell phenotypes. These changes in gene and cytokine production reduced the inflammatory component of wound healing and increased the migration of pro-regenerative cells (neutrophils and macrophages) to the wound site. The application of FTY720 delivery using a biomaterial has demonstrated the ability of local delivery of FTY720 to promote local wound healing leveraging an immunomodulatory mechanism.